PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SIRUP FREISS INDOFOOD (Studi Kasus pada Konsumen Sirup Freiss Indofood di Kota Semarang) - Heninda Ellya Putri; Apriatni Endang Prihatini; Agung Budiatmo (Universitas Diponegoro, 2015)
Freiss Indofood syrup improvement with the selection of natural ingredients, minimize the use of synthetic ingredients, and addition the composition of honey. In terms of promotion, the company cooperate with other Indofood products to joint promotions. However, in reality Freiss Indofood syrup sales fluctuated and can not achieve the sales target. Therefore it is necessary to know how much influence the quality of products and the promotion on purchase decisions Freiss Indofood syrup. This type of research is explanatory research. The technique of collecting data using questionnaires distributed to 100 respondents with purposive sampling method with accidental sampling method. Data analysis consisted of validity, reliability, cross tabulation, correlation, coefficient of determination, simple linear regression, multiple linear regression, t test and F test using SPSS for Windows version 16.0. This research concluded that quality products and promotion have positive and significant effect to influence on purchasing decisions either partially or simultaneously. Promotion have greater influence than the quality products. Suggestions to Freiss Indofood syrup are to be more attention for tastes, needs and desires of consumers and increase the frequency of advertising impressions, increase the frequency of sales promotions.